(untitled) (Journal of Pure & Applied Sciences, 2022)
The goal of the current study considers the impact of Lorentz force and radiation on the reactive Casson-Nanofluid flow over a flow over a stretched surface with Soret impact. However, its industrial and technological applications are numerous but not limited to solar power, glass spinning, nuclear reactors, processing and packaging of food, etc. The flow being considered is a function of the stretched surface along its direction in line with a linearly changing velocity with such distance from a given immovable point. The partial differential equations describing the momentum, energy (heat) and mass transfer equations were transformed into non-linear ordinary differential equations in non-dimensional forms through the use of the similarity variables approach. The solution which was carried out through the application of the series approximation method is presented analytically. However, the Mathematica software was used in obtaining the numerical solutions. Thus, the impacts of physical parameters of the fluid were studied. The results indicated that: the velocity of fluid flow lessens due to the combined intensification of values of the non-Newtonian Casson fluid and magnetic field parameters. An upsurge in Grashof heat and radiation factors yields a rise in the velocity. Influence of collective Casson and magnetic parameters leads to an appreciation of heat distribution. Also, the concentration field declines as both the Casson and Schmidt parameters improve. The diminishing distribution fields of both the wall energy and mass gradients are functions of the appreciating values of the non-Newtonian number.